Quantum phenomena in nanostructures. Issue 1 (January 2021) - Dev, B N
Abstract: Quantum phenomena in nanostructures, especially epitaxial structures, are utilized for the fabrication of quantum devices. Here we discuss self organized growth of epitaxial quantum structures on silicon and their electronic structures, such as electronic density of states, and electronic transport in such systems. We discuss nanodots and nanowires, or an equivalent of zero-dimensional (0D) and one-dimensional (1D) structures in more details, and in general structures in all dimensional cross-over regimes. Further arrangements of quantum dots (QDs) in particular structures offers to form quantum bits and quantum dot molecules (QDMs). This could lead to exploration of new physics and new quantum devices.